A systematic review on the effects of local antimicrobials as adjuncts to subgingival debridement, compared with subgingival debridement alone, in the treatment of chronic periodontitis. (16th January 2013) - Matesanz‐Pérez, Paula; García‐Gargallo, María; Figuero, Elena; Bascones‐Martínez, Antonio; Sanz, Mariano; Herrera, David
Abstract Aims To update the existing scientific evidence on the efficacy of local antimicrobials as adjuncts to subgingival debridement in the treatment of chronic periodontitis. Material and Methods Fifty‐six papers were selected, reporting data from 52 different investigations. All the studies reported changes in probing pocket depth (PPD) and clinical attachment level (CAL) and most in plaque index (PlI) and/or bleeding on probing (BOP). Meta‐analyses were performed with the data retrieved from the studies fulfilling the inclusion criteria. Results The overall effect of the subgingival application of antimicrobials was statistically significant (p = 0.000) for both changes in PPD and CAL with a weighted mean difference (WMD) of −0.407 and −0.310 mm respectively. No significant differences occurred for changes in BOP and PlI. Subgingival application of tetracycline fibres, sustained released doxycycline and minocycline demonstrated a significant benefit in PPD reduction (WMD between 0.5 and 0.7 mm). The rest of the tested outcomes demonstrated a high heterogeneity. The local application of chlorhexidine and metronidazole showed a minimal effect when compared with placebo (WMD between 0.1 and 0.4 mm). Conclusions The scientific evidence supports the adjunctive use of local antimicrobials to debridement in deep or recurrent periodontal sites, mostly when using vehicles with proven sustained release of the antimicrobial.